PENGUATAN KEGIATAN KEMASYARAKATAN BERBASIS PROGRAM KERJA KKN DI DESA GRINTING KECAMATAN TULANGAN KABUPATEN SIDOARJO - Muhammad Nurkholis Kholik; MIftahul Huda; Amirul Mukminin; Ubaid Aisyul Hana (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The focus of service activities in this KKN is to identify and improve the development of religious, educational, economic and social activities in the Grinting Village area. The method used in this service is PAR (Participatory Action Research). Which has three stages, begin a Research, which is the problem identification stage. Then the Action, which is the implementation stage, last is Participatory, where all parties are involved in carrying out the existing program. The results of the team's service were first, four work programs were successfully implemented, namely in the fields of religion, education, economics and health as a joint learning effort in solving problems faced by society. Second, the implementation of the work program received a positive response from the government and the community so that everything ran smoothly. Third, there are outputs and outcomes such as increasing religious activities, emerging creativity in learning-age children, as well as understanding and encouraging digital market innovation in Grinting Village.